236U and 239, 240Pu ratios from soils around an Australian nuclear weapons test site. (January 2016) - Tims, S.G.; Froehlich, M.B.; Fifield, L.K.; Wallner, A.; De Cesare, M.
Abstract: The isotopes 236 U, 239 Pu and 240 Pu are present in surface soils as a result of global fallout from nuclear weapons tests carried out in the 1950's and 1960's. These isotopes potentially constitute artificial tracers of recent soil erosion and sediment movement. Only Accelerator Mass Spectrometry has the requisite sensitivity to measure all three isotopes at these environmental levels. Coupled with its relatively high throughput capabilities, this makes it feasible to conduct studies of erosion across the geographical extent of the Australian continent. In the Australian context, however, global fallout is not the only source of these isotopes. As part of its weapons development program the United Kingdom carried out a series of atmospheric and surface nuclear weapons tests at Maralinga, South Australia in 1956 and 1957. The tests have made a significant contribution to the Pu isotopic abundances present in the region around Maralinga and out to distances ∼1000 km, and impact on the assessment techniques used in the soil and sediment tracer studies. Quantification of the relative fallout contribution derived from detonations at Maralinga is complicated owing to significant contamination around the test site from numerous nuclear weapons safety trials that were also carried out around the site. We show that 236 U can provide new information on the component of the fallout that is derived from the local nuclear weapons tests, and highlight the potential of 236 U as a new fallout tracer. Highlights: Measured 236 U inventories around the Maralinga Test Nuclear weapons test site. Comparison of 236 U and 239 Pu soil depth profiles at Maralinga. Differences in 236 U and 239 Pu inventories indicate most Pu fallout is from the safety trials, rather than the weapons tests.